Poly[oligo(ethylene glycol) methacrylate]-b-poly[(vinyl benzyl trimethylammonium chloride)] Based Multifunctional Hybrid Nanostructures Encapsulating Magnetic Nanoparticles and DNA - Chroni, Angeliki (Polymers (Basel), 2020)
We report on the preparation of novel and multifunctional hybrid spherical-shaped nanostructures involving a double-hydrophilic block copolymer, namely the neutral cationic poly[oligo(ethylene glycol) methacrylate]-b-poly[(vinyl benzyl trimethylammonium chloride)] (POEGMA-b-PVBTMAC) diblock copolymer, initially complexed with hydrophilic anionic magnetic nanoparticles (MNPs), and subsequently, with short deoxyribonucleic acid (113 bases DNA). The POEGMA-b-PVBTMAC copolymer, the copolymer/MNPs and the copolymer/MNPs/DNA tricomponent hybrid electrostatic complexes were studied by dynamic/electrophoretic light scattering (DLS/ELS) and cryogenic transmission electron microscopy (cryo-TEM) techniques for the determination of their structure and solution properties. The MNPs were complexed efficiently with the oppositely charged diblock chains, leading to well-defined hybrid organic–inorganic spherical-shaped nanostructures. A significant aggregation tendency of the MNPs is noticed in cryo-TEM measurements after the electrostatic complexation of DNA, implying an accumulation of the DNA macromolecules on the surface of the hybrid tricomponent complexes. Magnetophoretic experiments verified that the MNPs maintain their magnetic properties after the complexation initially with the copolymer, and subsequently, within the block polyelectrolyte/MNPs/DNA nanostructures.